Integration of Disaster Education Through Learning of Social Studies in Junior High School in Effort to Prepare Disaster Resilient Students - Logayah, Dina Siti; Maryani, Enok; Ruimat, Mamat; Wiyanarti, Erlina (Jurnal Pendidikan Ilmu Sosial, 2022)
This research aims to prepare students to be ready to face disasters in their surrounding environment through disaster education. Even though preparing for disaster preparedness requires a long process, disaster education is very important to be implemented from basic to higher education, especially for countries with high levels of disaster vulnerability. The research method used is the literature method or literature review, namely by reviewing relevant literature. The results of data analysis show that disaster education can be integrated into social studies learning through 6 basic competency standards, and can be maximized by utilizing the environment around students as a source of disaster learning.  Disaster education in the Philippines is an effort to provide knowledge, skills and awareness to the public regarding natural disasters and their management. Disaster education improves society's ability to face, respond to, and recover from disasters.